Individual Factor of Blame Attribution in Situations of Violence Against Women - Vinnikova, A.Yu; Obidin, I.Yu (Socialʹnaâ Psihologiâ i Obŝestvo, 2024)
Objective. Analysis of the relationship between the individual psychological and sociodemographic characteristics of bystanders and their tendency to blame the victim. Background. Despite the fact that the responsibility for violence always on the agressor, blaming the victim is still a common phenomenon. Currently, the factors of victim blaming are widely studied abroad, but there are contradictions in the obtained data. There is an insufficient amount of research in Russia, and existing research mainly concerns global factors, such as the role of the media. Study design. The study examined individual psychological and social-demographic characteristics of the groups of bystanders who choose different strategies of blame attribution in a situation of violence. According to the results of the author's questionnaire, respondents were divided into three groups: blaming the aggressor, blaming the victim and inconsistent in blaming. The groups were compared by self-attitude, empathy, basic beliefs, sociodemographic characteristics and awareness of various aspects of the problem of violence. The differences between the groups were verified through the comparative analysis. Participants. Russian sample, 91 people (38,5% of men, 61,5% of women) from 19 to 68 years old (M = 32,3; SD = 13,6). Measurements. Vignettes containing descriptions of violent situations and options for attributing blame to participants in the situations. Author's questionnaire for sociodemographic data and data about awareness of violence, personal experience related to this topic. Multidimensional questionnaire of self-attitude research by S.R. Panteleev, "Diagnostics of empathy level" by V.V. Boyko, Russian version of World assumptions scale by M.A. Padun, A.V. Kotelnikova. Results. We found significant differences between the groups according to the characteristics of self-attitude: the level of self-attachment in the group blaming the aggressor is significantly different from the level of self-attachment in other groups, the level of self-control in the group blaming the aggressor is significantly different from the level of self-control in the group blaming the victim. Significant differences in the level of believes in a just world between the group blaming the aggressor and other groups have been revealed. There were no significant differences in the characteristics of empathy. The groups considered differ significantly in assessing the significance of the problem of violence, awareness of the phenomenon of victim-blaming, the presence of the professional, volunteer or studying experience of interacting with a victim of violence, age and place of residence. Conclusions. Identify the Individual factors of victim blaming in the Russian sample. The more the respondent believes in the just world, the higher the level of self-attachment and self-control, the more likely he is to blame the victim. The following individual factors are associated with a lower probability of victim-blaming: assessment of the problem of violence as more significant, awareness of the existence of such a phenomenon as "victim-blaming", the professional, volunteer or studying experience of interacting with a victim of violence, young age and living in a megalopolis. Цель. Изучение связи между индивидуальными психологическими и социально-демографическими особенностями сторонних наблюдателей ситуации насилия и тенденцией к обвинению жертвы. Контекст и актуальность. Несмотря на то, что ответственность за насилие всегда лежит на агрессоре, обвинение жертвы до сих пор является распространенным явлением, в частности в контексте домашнего насилия, что в свою очередь непосредственно сказывается на поведении жертвы. В настоящее время факторы виктимблейминга широко исследуются за рубежом, однако в полученных данных имеются противоречия. В России подобных исследований недостаточно, а существующие в основном касаются глобальных факторов. Дизайн исследования. Изучались индивидуально-психологические особенности и социально-демографические характеристики сторонних наблюдателей, которые выбирают различные стратегии обвинения одной из сторон в ситуации насилия. На основании атрибуции вины в исследуемых ситуациях выборка была разделена на три группы: обвиняющие агрессора, обвиняющие жертву и непоследовательные в обвинениях. Группы сравнивались по социально-демографическим характеристикам, информированности о различных аспектах проблемы насилия, самоотношению, эмпатии, базисным убеждениям. Участники. Российская выборка, 91 человек (38,5% мужчин, 61,5% женщин) от 19 до 68 лет. Методы (инструменты). Метод виньеток; авторская анкета, содержащая вопросы о социально-демографических характеристиках, об информированности о насилии и личном опыте, связанном с ним; многомерный опросник исследования самоотношения С.Р. Пантилеева; «Диагностика уровня эмпатии» В.В. Бойко; шкала базисных убеждений в адаптации М.А. Падун, А.В. Котельниковой. Результаты. По результатам исследования самоотношения выявлены достоверные различия в уровне саморуководства и самопривязанности между группой, обвиняющей агрессора, и другими группами. Выявлены значимые различия в уровне веры в справедливый мир между группой, обвиняющей агрессора, и другими группами. Значимых различий в характеристиках, связанных с эмпатией, не обнаружено. Рассмотренные группы сторонних наблюдателей достоверно различаются по оценке значимости проблемы насилия, информированности о явлении виктимблейминга, наличию учебного, профессионального или волонтерского опыта взаимодействия с пострадавшими, а также по возрасту и месту жительства. Основные выводы. Были выявлены индивидуальные факторы виктимблейминга: большая вероятность обвинения жертвы связана с большей верой в справедливость мира, большей уверенностью стороннего наблюдателя в том, что основным источником развития собственной личности, регулятором достижений и успехов является он сам (уровень саморуководства), а также высокой ригидностью Я-концепции, стремлением сохранить восприятие и оценку себя (уровень самопривязанности). В случаях, когда сторонний наблюдатель оценивает проблему насилия как очень значимую, информирован о существовании такого явления, как виктимблейминг, имеет профессиональный, волонтерский или учебный опыт взаимодействия с жертвой насилия, уровень виктимблейминга снижается, вина приписывается агрессору. Молодые люди и люди, проживающие в мегаполисах, менее склонны к возложению вины на жертву. Полученные результаты необходимо использовать при планировании и разработке программ профилактики виктимблейминга, формировании групп и мишеней воздействия.